Radially inflows and outflows of hydromagnetic viscous fluid between two narrowly flat disks - A. Naeem; Z. Abbas; M.Y. Rafiq (Results in Engineering)
The study of flow between two parallel flat disks has numerous practical applications in fields such as fluid machinery, cooling systems, and industrial processes. In this context, this paper investigates the laminar, radial flow of a viscous fluid between two flat disks under the influence of a magnetic field. An analytical solution for the velocity distribution of both radial inflows and outflows is derived using Jacobi elliptic sine-squared functions. For small Reynolds numbers, the velocity profiles exhibit a parabolic pattern, while higher Reynolds numbers lead to transitions toward turbulence. Symmetric flow behavior is observed for both inflows and outflows, and streamlines are employed to illustrate the flow patterns. Additionally, the pressure and shear stress distributions follow an inverse-square law, with the friction factor remaining unchanged. These findings are significant for understanding and optimizing non-uniform open-channel flows impacted by nonlinear inertia, with real-world applications in designing efficient fluid transport systems, enhancing heat exchangers, and improving the performance of devices such as centrifugal pumps and turbines.